Market reaction of the business cooperation with IT service provider: an investigation of IBM. Issue 12 (31st July 2020) - Huang, Cheng-Kui; Lee, Kwo-Whei; Chou, Chien-Huei
Abstract : Purpose: Since business competition has become more intense throughout the world, most enterprises are seeking to engage in business cooperation with other partners in order to enhance their competitive strengths. However, they do not necessarily develop mature information technologies' (ITs) capabilities and skills internally but rather outsource them to IT providers. Therefore, the benefits received by firms which adopt the approach of business cooperation with IT providers have become an interesting issue for managers and shareholders. Design/methodology/approach: This study adopted an event study methodology for apprising the short-term business value from the stock market. The authors predicted that investors will react as they receive news coverage about the strategy of business cooperation between outsourcing firms and an IT provider, International Business Machines (IBM) Corporation. The authors then collected all news coverage regarding the firms which had announced business cooperation with IBM and observed different types of abnormal returns. Findings: On analyzing 53 announcements of cooperation with IBM from 2008 to 2016, the authors found that the announcement of business cooperation had a significantly positive influence on companies' market value. Originality/value: To the best of the authors' knowledge, this is the first study to investigate the issue for market reaction to the announcement of business cooperation with IBM.